Deconstructing Rahwana’s Alternate Character in Neelakantan's Rahwana: Kisah Rahasia through Derrida’s Perspective - Wardani, Vistaria Kusuma; Triyono, Sulis (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
This study explored the deconstruction of Rahwana's 'Ravana' character in Anand Neelakantan's novel Rahwana: Kisah Rahasia through the lens of Jacques Derrida's deconstruction theory. The novel narrates Rahwana's journey as he strives to elevate the status of his family and nation. Derrida's deconstruction approach was selected to uncover the complex layers within literary texts, challenging traditional interpretations. As a descriptive-qualitative study, this research analyzed textual evidence from the novel to compare the initial portrayal of Rahwana with his deconstructed character. The findings indicated a complex duality in Rahwana's depiction: while his traditional characterization was marked by ruthlessness, arbitrariness, defiance of divine authority, and ambition, the deconstructed perspective revealed his compassionate, just, devout, and even pessimistic dimensions. These contrasting portrayals underscored the fluidity of Rahwana's character, which was uncovered through the deconstruction. The novelty of this research is to rethink of Rahwana's alternate character from his traditional character embedded in popular puppet stories through a deconstruction approach. Finally, the story of Rahwana has various versions, particularly related to Sinta's abduction. Some stories reveal Rahwana's love for Sinta in romantic ways, while in Neelakantan's novel Rahwana: Kisah Rahasia, Rahwana's love is depicted as a father's love for his daughter, not as a couple romance.